CROSS-CULTURAL COMMUNICATION OF CONCEPTS IN MODIAIN - Neupane, Nabaraj (Universitas Pendidikan Indonesia, 2021)
Translation involves communication across languages and cultures. When one translates, s/he is involved in cross-cultural communication that is necessary in the current world scenario of globalization. English has been a global lingua franca that lubricates communication in the multilingual and multicultural communities. In this context, some Nepali novels have been translated into English, including Modiain that is the corpus of the present study. This study aims to explore and examine strategies used in translating cultural concepts (CCs) from Nepali into English. To achieve the set objective, I have employed corpus-based research design that uses parallel corpora consisting of Nepali-English pair of the selected novel. I investigated CCs in the original version and examined their translation counterparts in light of the set strategies such as translation by a more general term, a more neutral term, cultural substitution, loan terms, paraphrase, omission and illustration. The findings reveal that the use of the strategies poses pitfalls in transferring senses of the CCs across languages and cultures in one way or the other. This implies that the translators should be aware of the bilingual and bicultural sensitivities and sensibilities while translating CCs. Further implication of the study is that the course developers of applied linguistics, especially translation studies, should pay due attention while designing the courses towards the cross-cultural communicability of the CCs.